Biosynthetic gene cluster identification and biological activity of lucilactaene from Fusarium sp. RK97-94. Issue 6 (2nd June 2020) - Kato, Sho; Motoyama, Takayuki; Futamura, Yushi; Uramoto, Masakazu; Nogawa, Toshihiko; Hayashi, Toshiaki; Hirota, Hiroshi; Tanaka, Akira; Takahashi-Ando, Naoko; Kamakura, Takashi; Osada, Hiroyuki
ABSTRACT: We identified the biosynthetic gene cluster for lucilactaene, a cell cycle inhibitor from a filamentous fungus Fusarium sp. RK 97–94. The luc1 knockout strain accumulated demethylated analogs, indicating the involvement of Luc1 methyltransferase in lucilactaene biosynthesis. Lucilactaene showed potent antimalarial activity. Our data suggested that methylation and ether ring formation are essential for its potent antimalarial activity.